Markerless Lung Tumor Motion Tracking by Dynamic Decomposition of X-Ray Image Intensity. (8th December 2013) - Homma, Noriyasu; Takai, Yoshihiro; Endo, Haruna; Ichiji, Kei; Narita, Yuichiro; Zhang, Xiaoyong; Sakai, Masao; Osanai, Makoto; Abe, Makoto; Sugita, Norihiro; Yoshizawa, Makoto
Abstract : We propose a new markerless tracking technique of lung tumor motion by using an X-ray fluoroscopic image sequence for real-time image-guided radiation therapy (IGRT). A core innovation of the new technique is to extract a moving tumor intensity component from the fluoroscopic image intensity. The fluoroscopic intensity is the superimposition of intensity components of all the structures passed through by the X-ray. The tumor can then be extracted by decomposing the fluoroscopic intensity into the tumor intensity component and the others. The decomposition problem for more than two structures is ill posed, but it can be transformed into a well-posed one by temporally accumulating constraints that must be satisfied by the decomposed moving tumor component and the rest of the intensity components. The extracted tumor image can then be used to achieve accurate tumor motion tracking without implanted markers that are widely used in the current tracking techniques. The performance evaluation showed that the extraction error was sufficiently small and the extracted tumor tracking achieved a high and sufficient accuracy less than 1 mm for clinical datasets. These results clearly demonstrate the usefulness of the proposed method for markerless tumor motion tracking.